DEVELOPMENT OF THE HOTEL AND RESTAURANT BUSINESS IN UKRAINE IN THE CONDITIONS OF EUROPEAN INTEGRATION (Development Service Industry Management, 2025)
The article analyzes the current state and main trends in the development of the hotel and restaurant business in Ukraine in the context of European integration. The key challenges facing Ukrainian hospitality businesses are outlined, in particular the need to improve service quality standards, adaptation to European requirements for environmental sustainability, digitalization of personnel management, the personnel problem and attracting foreign investment. Particular attention is paid to improving the quality standards of hotel and restaurant services in accordance with European requirements. It is noted that Ukrainian enterprises are forced to adapt to international certifications, such as HACCP, ISO and others, which allows ensuring food safety, improving the quality of services and increasing the level of trust from foreign tourists.Also, the problem of staffing is considered, which remains one of the main challenges for the development of the hospitality sector. European standards require highly qualified employees, knowledge of foreign languages, mastery of modern technologies and a deep understanding of the cultural characteristics of guests. In this regard, the importance of modernizing educational programs, implementing a dual system of training, and actively involving young professionals in international internships is emphasized.The article separately analyzes the problem of attracting investment, which is one of the key factors in the restoration and development of the hotel and restaurant sector after the end of the war. European integration opens up new opportunities for cooperation with international investors, which contributes to the modernization of infrastructure, the construction of new hotels, and improving the quality of service. However, creating a favorable investment climate requires ensuring transparency in business, protecting investor rights, and developing public-private partnerships.In conclusion, it is noted that the development of the hotel and restaurant business in Ukraine in the context of European integration requires a comprehensive approach, including adaptation to international standards, digitalization, attracting investment, greening the business, and improving the level of personnel qualifications. Only with comprehensive support and active integration into the European market will the Ukrainian hospitality sector be able to become competitive and attractive to international tourists and partners.
Keywords: hotel and restaurant business; European integration; quality standards; digitalization; environmental sustainability; investments; human resources policy; international cooperation; professional education; innovative technologies; competitiveness; HACCP certification; tourist attractiveness